Lithium oxide precursor solution for coating electrode active material and preparation method thereof

By using a lithium oxide precursor solution containing specific concentrations of Li and M elements, the solution is easy to handle in the atmosphere and coated on the surface of the electrode active material to form a coating layer, solving the problem of high interface resistance in all-solid lithium batteries and improving battery characteristics and coverage ratio.

CN115701669BActive Publication Date: 2025-04-25DOWA ELECTRONICS MATERIALS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210921735.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-07-01
Filing Date
2022-08-02
Publication Date
2025-04-25
Estimated Expiration
2042-08-02

AI Technical Summary

Technical Problem

In all-solid lithium batteries, high resistance areas are easily formed at the interface between the electrode active substance and the solid electrolyte, resulting in deterioration of battery characteristics. In the prior art, the coating ratio of the lithium niobate precursor solution used to form a coating layer formed on the surface of the electrode active material is insufficient. At the same time, a lithium oxide precursor solution that is easily treated in the atmosphere is sought on the market.

Method used

A lithium oxide-containing precursor solution for coating the electrode active material is provided, which contains 0.1 mass % or more and 5.0 mass % or less, 0.05 mass % or more and 35 mass % or less, and water (such as Nb, F, Fe, P, etc.), 60 mass % or more and 98.4 mass % or less, and the absorbance at a wavelength of 660 nm is 0.1 or less, and the surface energy is 72 mN/m or less. This solution is coated on the surface of the electrode active material powder and dried to form a coating layer, which increases the coating rate and is easy to process in the atmosphere.

Benefits of technology

The coating rate of the surface coating layer of the electrode active material is improved, the interface resistance is reduced, the battery characteristics of all-solid lithium batteries are improved, and the production process is simplified because the solution is easy to process in the atmosphere.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115701669B_ABST
    Figure CN115701669B_ABST
Patent Text Reader

Abstract

A lithium-containing oxide precursor solution for coating an electrode active material and a manufacturing method thereof. A lithium-containing oxide precursor solution for coating an electrode active material, when applied to the surface of the powder of the electrode active material and dried to form a coating layer, can improve the coating rate of the coating layer, and uses a solution mainly composed of water as a solvent, which is easy to handle in the atmosphere. Provided is a lithium-containing oxide precursor solution for coating an electrode active material, comprising 0.1% by mass or more and 5.0% by mass or less of Li, 0.05% by mass or more and 35% by mass or less of at least one element selected from Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, I, 60% by mass or more and 98.4% by mass or less of water, the lithium-containing oxide precursor solution for coating an electrode active material having an absorbance value of less than 0.1 at a wavelength of 660nm, and a surface energy value of less than 72mN / m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium-containing oxide precursor solution used for coating an electrode active material used in a lithium secondary battery with a lithium-containing oxide and a production method thereof. Background Art

[0002] Lithium secondary batteries have the characteristics of high energy density and the ability to operate at high voltage. Therefore, they are used in information devices such as portable phones as secondary batteries that are easy to achieve small and light weight. In addition, in recent years, the demand for large-scale power secondary batteries such as secondary batteries for hybrid vehicles has also increased.

[0003] For example, in lithium-ion secondary batteries, a non-aqueous solvent electrolyte obtained by dissolving a salt in an organic solvent is generally used as an electrolyte. However, since the non-aqueous solvent electrolyte is a flammable electrolyte, lithium-ion secondary batteries need to solve safety issues. In order to ensure this safety, for example, countermeasures such as assembling safety devices in lithium-ion secondary batteries have been implemented. In addition, as a more fundamental solution, a method of making the above-mentioned electrolyte into a non-flammable electrolyte, that is, using a solid electrolyte as a lithium ion conductor to make an all-solid-state lithium battery is proposed.

[0004] Generally speaking, the electrode reaction of a battery occurs at the interface between an electrode active material and an electrolyte. In the present invention, the electrode active material is a concept including positive electrode active materials and negative electrode active materials.

[0005] Here, when the electrolyte uses a liquid electrolyte, the electrode containing the electrode active material is immersed in the liquid electrolyte, so that the liquid electrolyte penetrates between the active material particles to form a reaction interface. On the other hand, when the electrolyte uses a solid electrolyte, since the solid electrolyte does not have such a mechanism for penetrating between the active material particles, it is necessary to mix the powder containing the electrode active material particles with the powder of the solid electrolyte in advance. Therefore, the electrode of the all-solid-state lithium battery is usually a mixture of the powder of the electrode active material and the solid electrolyte.

[0006] However, in an all-solid-state lithium battery, a high resistance site is formed at the interface between the electrode active material and the solid electrolyte, and the interface resistance is easily increased. In order to avoid this situation, there is a method of reducing the interface resistance by coating the surface of the electrode active material with a lithium-containing oxide. For example, the prior art documents 1 and 2 propose a technology of forming a lithium niobate coating layer on the surface of the powder of the electrode active material by applying a lithium niobate precursor solution as a lithium oxide to the surface of the powder and drying it.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2015-56307

[0010] Patent Document 2: Japanese Patent Application Publication No. 2019-145261 Summary of the invention

[0011] Problem that the invention aims to solve

[0012] However, according to the research of the inventors, the coating layer formed on the surface of the powder particles of the electrode active material using the lithium niobate precursor solution described in the prior art sometimes has insufficient coverage. Therefore, it was found that in the electrode active material, high resistance sites are formed from sites that are not fully covered by the coating layer, resulting in a problem of deterioration of the battery characteristics of the all-solid-state lithium battery.

[0013] On the other hand, the market is looking for a lithium-containing oxide precursor solution that can be easily handled in the atmosphere and that uses a solution mainly containing water as a solvent.

[0014] The present invention was completed under the above circumstances, and the problem to be solved is to provide: a lithium oxide precursor solution for coating electrode active materials of lithium secondary batteries such as all-solid-state lithium batteries and lithium ion secondary batteries, which can improve the coverage rate of the coating layer when it is coated on the powder surface of the electrode active material and dried to form a coating layer, and uses a solution mainly composed of water as a solvent and is easy to handle in the atmosphere.

[0015] Solutions for solving problems

[0016] The inventors of the present invention have conducted in-depth research to solve the above-mentioned problems, and as a result, they have come up with the following lithium-containing oxide precursor solution for coating electrode active materials, which contains a specified amount of Li, a specified amount of at least one element selected from Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, and I (sometimes referred to as "M element" in the present invention), and contains water in an amount of 60% by mass or more and 98.4% by mass or less. The lithium-containing oxide precursor solution for coating electrode active materials has an absorbance of less than 0.1 at a wavelength of 660 nm, and a surface energy (the same concept as surface tension, but referred to as "surface energy" in the present invention) of less than 72 mN / m.

[0017] It was also found that when the lithium oxide precursor solution for coating the electrode active material is applied to the powder surface of the electrode active material and dried to form a coating layer, the coverage rate of the coating layer is improved, and the lithium oxide precursor solution for coating the electrode active material is easy to handle in the atmosphere, thereby completing the present invention.

[0018] That is, the first invention for solving the above-mentioned problems is:

[0019] A lithium oxide precursor solution for coating an electrode active material, comprising 0.1 mass % or more and 5.0 mass % or less of Li,

[0020] The invention contains 0.05 mass % or more and 35 mass % or less of at least one M element selected from the group consisting of Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, and I,

[0021] contains 60 mass % or more and 98.4 mass % or less of water,

[0022] The lithium oxide precursor solution used for coating the electrode active material has an absorbance value of 0.1 or less at a wavelength of 660 nm.

[0023] The value of the surface energy is 72 mN / m or less.

[0024] The second invention is:

[0025] According to the lithium-containing oxide precursor solution for coating an electrode active material according to the first invention, the value of the polar component of the surface energy is 0 mN / m or more and 45 mN / m or less.

[0026] The third invention is:

[0027] In the lithium-containing oxide precursor solution for coating an electrode active material according to the first or second invention, the value of Li / M (molar ratio) of the Li to the M element is 0.36 or more and 11.2 or less.

[0028] The fourth invention is:

[0029] In the lithium-containing oxide precursor solution for coating an electrode active material according to the first or second invention, a value of Li / Nb (molar ratio) of the Li and Nb is 0.90 or more and 1.40 or less.

[0030] The fifth invention is:

[0031] In the lithium-containing oxide precursor solution for coating an electrode active material according to the first or second invention, a value of Li / P (molar ratio) of the Li and P is 0.90 or more and 1.40 or less.

[0032] The sixth invention is:

[0033] According to any one of the first to fifth inventions, the lithium-containing oxide precursor solution for coating an electrode active material has a surface energy value of 15 mN / m or more and 40 mN / m or less.

[0034] The seventh invention is:

[0035] The lithium-containing oxide precursor solution for coating an electrode active material according to any one of the first to sixth inventions, comprising 0.01 mass % or more and 20.0 mass % or less of a surfactant.

[0036] The eighth invention is:

[0037] In the lithium-containing oxide precursor solution for coating an electrode active material according to the seventh invention, the surfactant is a nonionic surfactant.

[0038] The ninth invention is:

[0039] A method for preparing a lithium oxide precursor solution for coating an electrode active material comprises the following steps:

[0040] a dissolving step of dissolving lithium and at least one element selected from the group consisting of Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, and I in a solvent mainly composed of water that constitutes the lithium-containing oxide precursor solution for coating the electrode active material; and

[0041] The surface energy adjustment step is to adjust the surface energy value of the solvent mainly composed of water constituting the lithium-containing oxide precursor solution for coating the electrode active material to 72 mN / m or less.

[0042] However, either the dissolution step or the surface energy adjustment step may be performed first.

[0043] The tenth invention is:

[0044] A method for preparing a lithium oxide precursor solution for coating an electrode active material comprises the following steps:

[0045] A dissolving step of dissolving lithium and at least one element selected from the group consisting of Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, and I in a solvent mainly composed of water that constitutes the lithium-containing oxide precursor solution for coating the electrode active material;

[0046] a surface energy adjustment step of adjusting the surface energy value of the water-based solvent constituting the lithium-containing oxide precursor solution for coating the electrode active material to 72 mN / m or less; and

[0047] A filtration step is to filter the solution obtained after the above-mentioned dissolution step.

[0048] However, either the dissolution step or the surface energy adjustment step may be performed first.

[0049] The eleventh invention is:

[0050] The method for producing a lithium oxide precursor solution for coating an electrode active material according to the ninth or tenth invention is characterized in that in the surface energy adjustment step, the value of the polar component in the surface energy is adjusted to be greater than 0 mN / m and less than 45 mN / m.

[0051] The twelfth invention is:

[0052] The method for producing a lithium-containing oxide precursor solution for coating an electrode active material according to any one of the ninth to eleventh inventions, wherein the value of the surface energy is adjusted by adding a surfactant.

[0053] The thirteenth invention is:

[0054] According to the method for producing a lithium-containing oxide precursor solution for coating an electrode active material according to the twelfth invention, the surfactant is a nonionic surfactant.

[0055] Effects of the Invention

[0056] When the lithium-containing oxide precursor solution for coating the electrode active material of the present invention is applied to the surface of the powder of the electrode active material and dried to form a coating layer, the coverage rate of the coating layer can be increased. In addition, the lithium-containing oxide precursor solution for coating the electrode active material of the present invention is easy to handle in the atmosphere. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a graph showing the relationship between the surface energy value and the coverage rate of a lithium-containing oxide precursor solution used for coating an electrode active material.

[0058] Figure 2 This is a diagram showing the relationship between the value of the polar component in the surface energy and the coverage rate of a lithium-containing oxide precursor solution used for coating an electrode active material.

[0059] Figure 3 It means that the lithium oxide precursor solution used to coat the electrode active material is placed on LiNi 1 / 3 Co 1 / 3 Mn 1 / 3A graph showing the relationship between the value of cosθ and the coverage when the value of the contact angle on an O2 sputtered film-formed substrate is θ (sometimes referred to as "LNCM (111) substrate" in the present invention. The numbers in parentheses represent the composition ratio of Ni, Co, and Mn).

[0060] Figure 4 This is a graph showing the results of measuring the absorbance of the precursor solutions described in Examples 2, 5, and 8 at a wavelength of 400 to 700 nm. DETAILED DESCRIPTION

[0061] The lithium-containing oxide precursor solution for coating an electrode active material according to the present invention (sometimes referred to as "precursor solution" in the present invention) is described in the order of [1] the lithium-containing oxide precursor solution for coating an electrode active material, and [2] the method for producing the lithium-containing oxide precursor solution for coating an electrode active material. In addition, in the present invention, the electrode active material refers to a concept including positive electrode active materials and negative electrode active materials.

[0062] [1] Lithium oxide precursor solution for coating electrode active material

[0063] The precursor solution described in the present invention contains Li in an amount of not less than 0.1 mass % and not more than 5.0 mass %, not less than 0.05 mass % and not more than 35 mass % of at least one element selected from the group consisting of Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, and I, and not less than 60 mass % and not more than 98.4 mass % of water. The precursor solution has an absorbance value of not more than 0.1 at a wavelength of 660 nm and a surface energy value of not more than 72 mN / m.

[0064] In the precursor solution of the present invention, by setting the concentration of Li to 0.1 mass % or more, a precursor solution containing a lithium oxide covering layer can be obtained.

[0065] On the other hand, from the viewpoint of ensuring solubility in the solvent contained in the precursor solution, the concentration of Li is set to 5.0 mass % or less. From this viewpoint, the concentration of Li is more preferably set to 1.0 mass % or less.

[0066] The concentration of Li in the precursor solution can be obtained by, for example, analyzing the components of the precursor solution using inductively coupled plasma emission spectrometry.

[0067] The precursor solution of the present invention can obtain a precursor solution of an oxide coating layer having lithium conductivity by simultaneously containing Li and M elements, wherein the M element is at least one additional element selected from Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, and I. Among them, Nb and P are preferred M elements from the viewpoint of improving the voltage resistance of the coating layer. If the voltage resistance of the coating layer is high, the battery can be operated at a higher voltage, for example, the charging time can be shortened.

[0068] In addition, if the concentration of the M element in the precursor solution is less than 0.05 mass %, the concentration of Li in the precursor solution becomes excessive, and the possibility of generating and mixing non-lithium ion conductive lithium hydroxide when forming the coating layer increases. Therefore, from the viewpoint of ensuring the lithium ion conductivity of the formed coating layer, the concentration of the M element in the precursor solution is preferably 0.05 mass % or more.

[0069] On the other hand, from the viewpoint of ensuring solubility in the solvent contained in the precursor solution, the concentration of the M element is set to 35 mass % or less. From this viewpoint, the concentration of the M element is more preferably set to 10 mass % or less.

[0070] Here, a plurality of M elements may be contained. In this case, for the above-mentioned reasons, the total concentration of the plurality of M elements is preferably 0.05 mass % to 35 mass %, and more preferably 0.05 mass % to 10 mass %.

[0071] It should be noted that the concentration of the M element in the precursor solution can be obtained by, for example, analyzing the components of the precursor solution using inductively coupled plasma emission spectrometry.

[0072] In the precursor solution of the present invention, the molar ratio of Li to M element, i.e., the value of Li / M, is preferably set to be greater than 0.36 and less than 11.2. This is because: if the value of Li / M is greater than 0.36, the amount of lithium in the final lithium-containing oxide coating layer can be fully ensured, and the lithium ion conductivity of the coating layer can be ensured, so it is preferred. In addition, if the value of Li / M is less than 11.2, lithium hydroxide and lithium nitrite with low lithium conductivity will not be mixed into the final lithium-containing oxide coating layer, and the lithium conductivity of the coating layer can be ensured, so it is preferred.

[0073] When Nb is used as the M element, from the viewpoint of ensuring the lithium ion conductivity of the coating layer, the value of Li / Nb is preferably 0.90 or more and 1.40 or less for the reasons described above.

[0074] When P is used as the M element, from the viewpoint of ensuring the lithium ion conductivity of the coating layer, the value of Li / P is preferably 0.90 or more and 1.40 or less for the reasons described above.

[0075] The precursor solution of the present invention uses a solution mainly containing water as a solvent.

[0076] Furthermore, by setting the water content in the precursor solution to 60% by mass or more, a precursor solution that is stable in the atmosphere is formed. As a result, the operation of coating the electrode active material using the precursor solution can be easily implemented in the atmosphere. On the other hand, by setting the water content to 98.4% by mass or less, when it is desired to obtain a coating layer of a specified film thickness, the increase in the amount of the precursor solution caused by the low concentration of the Li and M elements in the precursor solution can be avoided.

[0077] It should be noted that the water content in the precursor solution can be conveniently measured by volumetric titration using a Karl Fischer titrator.

[0078] The absorbance value of the precursor solution of the present invention at a wavelength of 660 nm is less than 0.1.

[0079] This is because the absorbance at a wavelength of 660 nm represents the intensity of scattered light caused by the microparticles present in the precursor solution. Therefore, in the precursor solution of the present invention, a high absorbance means a high concentration of microparticles present in the precursor solution (see, for example, JIS-K0101).

[0080] And, if the precursor solution with high concentration of the particles is coated on the electrode active material, the particles are attached to the surface of the electrode active material and the coating layer forms a concavo-convex shape, and the thickness of the coating layer becomes uneven. If the thickness of the coating layer becomes uneven, the film portion with insufficient thickness of the coating layer is generated, and then the uncoated position is generated, and the coverage rate is sometimes reduced.

[0081] According to the research conducted by the present inventors, if the absorbance of the precursor solution at a wavelength of 660 nm is 0.1 or less, the amount of fine particles in the precursor solution is sufficiently small, and the adverse effects on the uniformity of the coating layer thickness and the coverage rate are suppressed.

[0082] The absorbance value was obtained by setting the temperature of the precursor solution to 25° C. and measuring the absorbance at a wavelength of 660 nm using an ultraviolet-visible spectrophotometer.

[0083] In this case, the lower limit of the absorbance is 0.000. However, the detection limit of the ultraviolet-visible spectrophotometer used for the absorbance measurement is 0.001.

[0084] The surface energy of the precursor solution of the present invention is less than 72 mN / m.

[0085] This is because: by reducing the surface energy value of the precursor solution, the wettability with the electrode active material becomes good, and when the precursor solution is applied to the surface of the electrode active material, it will be uniformly wetted and spread, so the formed coating layer is uniform, the thin film portion is reduced, and thus the coverage rate is improved. In addition, by setting the surface energy value to 72mN / m or less, a sufficient coverage rate can be obtained.

[0086] On the other hand, if the value of the surface energy of the precursor solution is too small relative to the value of the surface energy of the electrode active material, the precursor solution is easily peeled off from the surface of the electrode active material. As a result, the possibility of the coating layer formed being non-uniform and the coverage rate being reduced is improved. Therefore, the surface energy is preferably more than 15mN / m.

[0087] The surface energy value of the precursor solution was measured by using an automatic surface tensiometer at 25°C.

[0088] Furthermore, the vast majority of surface energy is composed of a dispersion component and a polar component. The dispersion component is a force generated by the instantaneous charge shift between all molecules, and the polar component is a force generated by the charge shift between polar molecules (it can be considered that the hydrogen bond component is attributed to the polar component).

[0089] Furthermore, it is preferred to reduce the value of the polar component in the surface energy of the precursor solution of the present invention to less than 45mN / m. By reducing the value of the polar component to less than 45mN / m, the polar component of the surface energy of the precursor solution becomes a value similar to the polar component of the surface energy of the electrode active material, and therefore, the wettability of the precursor solution and the electrode active material becomes better. For example, the surface energy of lithium cobalt oxide, which is a representative electrode active material and a positive electrode active material, is 20.6mN / m, wherein the dispersion component is 18.4mN / m and the polar component is 2.2mN / m. On the other hand, the surface energy of pure water is 72.8mN / m, wherein the dispersion component is 21.8mN / m and the polar component is 51.0mN / m. That is, between water and the positive electrode active material, the deviation of the value of the polar component is particularly large. From this point of view, the present invention can obtain a significant effect by being applied to the positive electrode active material.

[0090] It should be noted that in order to measure the values ​​of the polar component and the dispersion component, the precursor solution was dropped onto the paraffin substrate at 25° C., and the contact angle was calculated using the θ / 2 method. The Young-Dupre formula was used to calculate the contact angle obtained, the surface energy value of the precursor solution measured using an automatic surface tensiometer, and the literature value of the surface energy of the paraffin.

[0091] Here, when the precursor solution that reduces the deviation of the value in the polar component is applied to the surface of the electrode active material, it will be further uniformly wetted and diffused, so the formed coating layer is homogenized and the coverage rate is improved. In other words, even in the case of having the same surface energy value as the precursor solution, the smaller the deviation of the value of the polar component, the better the wettability of the electrode active material surface, so when the precursor solution is applied to the surface of the electrode active material, it will be uniformly wetted and diffused, so the formed coating layer is homogenized and the coverage rate is improved.

[0092] From this viewpoint, the value of the polar component in the value of the surface energy of the precursor solution is preferably more than 0mN / m and less than 45mN / m. In addition, if the value of the polar component is more than 0mN / m and less than 15.0mN / m, then the value of the surface energy of the electrode active material is more similar, and wettability becomes good, so it is particularly preferred.

[0093] It should be noted that the method for measuring the value of the polarity component of the precursor solution is described in Example 1.

[0094] In addition, the wettability of the precursor solution of the present invention and the electrode active material can also be judged according to the contact angle of the precursor solution on the substrate of the same composition as the electrode active material. The contact angle is preferably below 60 °, more preferably below 50 °. If the contact angle of the precursor solution on the substrate is below 60 °, the wettability of the electrode active material with the composition of the substrate is good, therefore, when the precursor solution is applied to the surface of the electrode active material, uniform wetting and diffusion can be achieved, therefore, the formed coating layer is homogenized, and the coverage rate is improved.

[0095] It should be noted that the method for measuring the contact angle of the precursor solution on the substrate is described in Example 1.

[0096] The precursor solution of the present invention described above can be applied to the electrode active material powder and dried to manufacture an electrode active material having a coating layer. In addition, the precursor solution of the present invention does not contain components such as alkoxides that react with moisture in the atmosphere to generate precipitates that are insoluble in the solution, so there are the following advantages: it can be processed under the atmosphere without the need for dry atmosphere equipment such as a drying chamber. Furthermore, the wettability for the electrode active material is excellent, so the entire surface of the electrode active material can be coated without gaps by one coating, and the coverage rate is improved, so it is possible to suppress the formation of high resistance sites on the surface of the electrode active material that are generated from insufficiently coated sites.

[0097] [2] Method for producing a lithium oxide precursor solution for coating an electrode active material

[0098] The method for producing the precursor solution of the present invention is described in the order of (1) solvent, (2) lithium compound, (3) M element compound, and (4) method for producing the precursor solution.

[0099] (1) Solvent

[0100] As the solvent constituting the precursor solution of the present invention, various solvents can be used. However, as mentioned above, from the viewpoint of manufacturing a precursor solution that is stable in the atmosphere, a solvent mainly composed of water is used. From the viewpoints of raw material cost, environmental burden, workability, etc., it is also preferred to use a solvent mainly composed of water as the solvent.

[0101] Specifically, as the precursor solution of the present invention, the water content in the solvent is adjusted in such a manner that the precursor solution contains 60% by mass or more of water and is stable in the atmosphere. On the other hand, as the precursor solution, the water content contained is set to 98.4% by mass or less, so as to avoid an increase in the amount of the precursor solution due to a decrease in the precursor concentration.

[0102] Furthermore, in order to adjust the surface energy value of the precursor solution, the solvent of the precursor solution according to the present invention also preferably contains a surfactant.

[0103] (2) Lithium compounds

[0104] The lithium compound is not particularly limited as long as it is dissolved in the solvent to be used.

[0105] In particular, if a solvent mainly composed of water is used as the solvent, suitable examples include lithium salts such as lithium hydroxide (LiOH), lithium nitrate (LiNO3), lithium sulfate (Li2SO4), lithium carbonate, and lithium nitrite. From the perspective of not introducing impurities into the solution, lithium hydroxide is preferred.

[0106] (3) M element compounds

[0107] The M element compound is not particularly limited as long as it is dissolved in the solvent to be used.

[0108] In particular, when a solvent mainly composed of water is used as the solvent, in the case of an M element that can form a complex compound of the M element (sometimes referred to as "M element complex" in the present invention), it is preferred to use an M element complex. This is because: from the viewpoint of stable dissolution in a solvent mainly composed of water, an M element complex is preferred.

[0109] Among them, as the water-soluble M element complex, a peroxo complex of the M element can be preferably used. The peroxo complex of the M element does not contain carbon in its chemical structure, and therefore, no carbon remains in the coating film finally formed on the electrode active material, and is particularly suitable.

[0110] On the other hand, for example, in the identification of niobium peroxo complex in a solution containing lithium and niobium as the M element, it can be identified by measuring with the incident angle to a germanium prism set to 45° using a single reflection ATR method using an FT-IR device.

[0111] According to the results of this measurement, if the wavelength at 855 cm-1, which is attributed to the peroxy complex, -1 ±20cm -1 and 1650cm -1 ±10cm -1 If a peak is confirmed at , it can be considered that the niobium dissolved in the solution containing lithium and niobium is in the form of a niobium complex (specifically, a peroxo complex).

[0112] When P is used as the M element, it is preferable to use lithium phosphate, which is a compound of phosphorus and lithium and is water-soluble.

[0113] (4) Method for producing precursor solution

[0114] The method for producing the precursor solution is not particularly limited. Therefore, as an example of the production method, a case where Nb is used as the M element to produce a precursor solution containing a lithium and niobium complex is described in the order of <1> niobium dissolution step, <2> lithium dissolution step, <3> surface energy adjustment step, and <4> filtration step.

[0115] 〈1〉Niobium dissolution process

[0116] In the niobium dissolution step, niobic acid (Nb2O5·nH2O) is added to, for example, hydrogen peroxide water and mixed, and then a base such as ammonia water is added to make a transparent solution, thereby preparing a peroxo complex of niobium as a niobium compound, which is dissolved in a solvent mainly composed of water, which constitutes the lithium-containing oxide precursor solution for coating the electrode active material described in the present invention, to prepare a solution. As long as the peroxo complex of niobium can be synthesized, the mixing ratio of hydrogen peroxide water, niobic acid and a base such as ammonia water is not particularly limited.

[0117] When a peroxo complex of niobium is used as the niobium complex, when niobic acid is added to hydrogen peroxide water and mixed, the molar ratio of hydrogen peroxide to 1 mol of niobium is preferably set to 4 or more.

[0118] On the other hand, it is considered that the effect is saturated even if the molar ratio of hydrogen peroxide to 1 mol of niobium is greater than 30. Therefore, the molar ratio of hydrogen peroxide to 1 mol of niobium is preferably 20 or less, more preferably 15 or less.

[0119] In addition, when niobic acid is added to hydrogen peroxide water and mixed, the liquid temperature of the hydrogen peroxide water is preferably 0° C. or higher, and preferably 60° C. or lower from the viewpoint of avoiding decomposition of the hydrogen peroxide water.

[0120] During this mixing, niobic acid does not dissolve in the hydrogen peroxide solution, and a milky white suspension containing niobic acid can be obtained.

[0121] By adding a base such as aqueous ammonia to a suspension containing niobic acid and mixing the mixture, a transparent solution containing a peroxo complex of niobium can be obtained.

[0122] When adding aqueous ammonia as a base to the suspension containing niobic acid, it is preferred that the base be added so that the molar ratio of ammonia to 1 mol of niobium (ammonia / Nb) becomes 3 or more.

[0123] On the other hand, it is considered that the effect is saturated even if the molar ratio of ammonia to 1 mol of niobium is added to exceed 8. Therefore, the molar ratio of ammonia to 1 mol of niobium is preferably set to 6 or less.

[0124] When a base such as ammonia water is added to and mixed with a suspension containing niobic acid, the liquid temperature of the ammonia water or the like is preferably 0° C. or higher, and preferably 60° C. or lower from the viewpoint of avoiding volatilization of ammonia.

[0125] Furthermore, an alkaline aqueous solution may be added in addition to the aforementioned ammonia solution. In this case, the amount of the alkaline aqueous solution added is set to an amount such that the pH value of the aqueous solution after addition becomes 8 or more, preferably 9 or more. Adding a lithium hydroxide aqueous solution as the alkaline aqueous solution is a preferred configuration. On the other hand, if the pH value of the aqueous solution after adding the alkaline aqueous solution is 11 or more, the niobium complex may become unstable and an insoluble precipitate may be generated. Therefore, the above pH value is preferably less than 11.

[0126] <2> Lithium dissolution process

[0127] In the lithium dissolution step, a lithium compound is added to a solvent mainly composed of water, which constitutes the lithium-containing oxide precursor solution for covering the electrode active material according to the present invention, under an inert gas or air atmosphere, and dissolved to prepare a solution.

[0128] Here, in the lithium-containing oxide precursor solution for coating the electrode active material according to the present invention, if the amount of lithium is too small relative to the amount of niobium, when the coating layer of lithium niobate represented by LiNbO3 as the electrode active material is formed, the lithium conductivity of the coating layer may be reduced. On the other hand, if the amount of lithium is too large relative to the amount of niobium, lithium hydroxide and lithium nitrite, which do not have lithium conductivity, may be mixed into the lithium niobate as the coating layer, thereby reducing the lithium conductivity of the coating layer.

[0129] The above phenomenon of mixing lithium hydroxide and lithium nitrite which do not have lithium conductivity into the lithium niobate as a coating layer is sometimes not limited to the case where the M element is Nb. In order to avoid this mixing phenomenon, the value of the molar ratio of lithium to 1 mol of the M element (Li / M) is preferably 0.36 or more and 11.2 or less in terms of (molar ratio). Here, when the M element is Nb, the value of the molar ratio of lithium to 1 mol of niobium (Li / Nb) is more preferably 0.90 or more and 1.4 or less in terms of (molar ratio). Furthermore, when the M element is P, the value of the molar ratio of lithium to 1 mol of phosphorus (Li / P) is also more preferably 0.90 or more and 1.4 or less in terms of (molar ratio).

[0130] In addition, as the inert gas atmosphere, a nitrogen atmosphere is convenient.

[0131] It should be noted that either of the above-mentioned “〈1〉 niobium dissolution step” and “〈2〉 lithium dissolution step” may be performed first as desired, or they may be performed simultaneously.

[0132] 〈3〉Surface energy adjustment process

[0133] By adding an appropriate amount of a surfactant to the solvent constituting the precursor solution of the present invention, the value of the surface energy and the value of the polarity component of the solvent can be controlled.

[0134] Here, the surfactant refers to a substance having both a hydrophilic part and a hydrophobic (lipophilic) part in the molecule, and being adsorbed to the water-oil two-phase interface due to its hydrophilic-lipophilic balance to exhibit the effect of reducing the free energy (interfacial tension) of the interface.

[0135] As the surfactant, alcohols and nonionic surfactants having a nonionic polar group are preferred.

[0136] As the alcohol, an alcohol having three or more carbon atoms in the molecule, such as 1,2-propylene glycol and 1-butanol, which is soluble in water and can ensure the stability of the niobium complex is particularly preferred.

[0137] Furthermore, from the viewpoint of ensuring the stability of the niobium complex and the solubility in water, the alcohol preferably contains 3 to 6 carbon atoms in the molecule, and more preferably contains 3 or 4 carbon atoms.

[0138] If an alcohol having 3 or more carbon atoms in the molecule is added to the precursor solution of the present invention, the stability of the niobium complex in the solution can be ensured, which is preferred. In addition, an alcohol having 6 or less carbon atoms in the molecule has high solubility in water and is uniformly dispersed in a solution containing water, and the effect of reducing the surface energy of the solvent constituting the precursor solution of the present invention is easily obtained, which is preferred.

[0139] Alcohols having 4 or less carbon atoms in the molecule are particularly highly soluble in water, have high dispersion uniformity in a solution containing water, and are more preferably effective in reducing the surface energy of the solvent constituting the precursor solution of the present invention.

[0140] Specific examples of preferred alcohols include isopropanol, 1-propanol, 1-butanol, 2-methyl-1-propanol, 2-butanol, 2-methyl-2-propanol, 1-pentanol, 3-methyl-1-butanol, 2-methyl-1-butanol, 2,2-dimethyl-1-propanol, 2-pentanol, 3-methyl-2-butanol, 3-pentanol, 2-methyl-2-butanol, 3-methyl-1-pentanol, 4-methyl-1-pentanol, 2-methyl-2-pentanol, 3-methyl-2-pentanol, 4-methyl-2-pentanol, 2-methyl-3-pentanol, 3-methyl-3-pentanol, 2,2-dimethyl-1-butanol, 2,3-dimethyl-1-butanol, 3,3-dimethyl-1-butanol, 2,3-dimethyl-2-butanol, 3,3-dimethyl-2-butanol, and 2-ethyl-1-butanol.

[0141] As the nonionic surfactant, a surfactant having a nonionic polar group via an ether bond is preferred.

[0142] Specific examples of preferred nonionic surfactants include surfactants in which nonionic polar groups are formed via ether bonds, such as polyoxyethylene ethers (e.g., (registered trademark) FTERGENT 222F (manufactured by NEOS Corporation) with an ethylene oxide addition mole number of 22), polyoxyethylene alkyl ethers (e.g., (registered trademark) LEOCOL TD-120 (manufactured by Lion Corporation) with an ethylene oxide addition mole number of 12), diethylene glycol diethyl ether (e.g., (registered trademark) DEDG (manufactured by Nippon Emulsifier Co., Ltd.) with an ethylene oxide addition mole number of 2), and polyoxyethylene lauryl ether (e.g., (registered trademark) EMULGEN 108 (manufactured by Kao Corporation) with an ethylene oxide addition mole number of 6).

[0143] Furthermore, when the number of moles of ethylene oxide added to the nonionic surfactant is 10 or more, the dispersibility in water becomes good, and the effect of lowering the surface energy of the solvent constituting the precursor solution of the present invention is easily obtained, which is more preferred.

[0144] In order to control the value of the surface energy and polar component of the solvent constituting the precursor solution of the present invention, about the addition amount when adding one or more selected from alcohol and nonionic surfactant to the solvent, from the viewpoint of reducing the surface energy, controlling the value of the polar component, and improving the wettability with the electrode active material, a surfactant of 0.01 mass % or more and 20.0 mass % or less is included. If the surfactant is an alcohol, it is preferably 0.1 mass % or more and 20.0 mass % or less, and more preferably 1.0 mass % or more and 10.0 mass % or less. On the other hand, if the surfactant is a nonionic surfactant, it is preferably 0.01 mass % or more and 10.0 mass % or less, and more preferably 0.01 mass % or more and 5.0 mass % or less.

[0145] In this addition range, one or more selected from alcohol and nonionic surfactants are added while measuring the value of the surface energy and the value of the polar component of the solvent. In addition, the value of the surface energy is adjusted to 72mN / m or less. At this time, it is preferred to set the value of the polar component to 0mN / m or more and 45mN / m or less. The value of the surface energy is further preferably 15mN / m or more and 40mN / m or less, and at this time, it is more preferred to set the value of the polar component to 0mN / m or more and 15mN / m or less.

[0146] It should be noted that any one of the above-mentioned “〈1〉 niobium dissolution step”, “〈2〉 lithium dissolution step” and “〈3〉 surface energy adjustment step” may be performed first as desired.

[0147] 〈4〉Filtration process

[0148] A step of filtering the aqueous solution containing the lithium and niobium complex obtained by performing the above-mentioned "〈1〉 niobium dissolution step" and "〈2〉 lithium dissolution step" to obtain a precursor solution having an absorbance value of 0.1 or less at a wavelength of 660 nm.

[0149] However, when the absorbance value of the aqueous solution containing the lithium and niobium complex obtained by carrying out the "〈1〉 niobium dissolution step" and the "〈2〉 lithium dissolution step" at a wavelength of 660 nm has reached 0.1 or less and there is no need to carry out the "〈4〉 filtration step", the "〈4〉 filtration step" can be omitted.

[0150] It should be noted that the “〈4〉 filtering step” may be performed before or after the “〈3〉 surface energy adjusting step” as desired.

[0151] The filtering method is not particularly limited to centrifugal separation, filtering using various filters, etc. From the viewpoint of efficiency of removing particles and productivity, it is preferred to filter using a membrane filter. From the viewpoint of productivity, it is preferred to use a combination of pressurization and a filter, or a combination of pressurization and a filter having a fine pore size, such as fine filtration or ultrafiltration.

[0152] From the viewpoint of suppressing the productivity of filtration and the change of the characteristics of the solution, the liquid temperature during filtration is preferably 10°C or higher and 40°C or lower. This is because: if the liquid temperature is 10°C or higher, the viscosity of the solution decreases and the filtration speed can be ensured. This is because: if the liquid temperature is 40°C or lower, the decrease caused by the volatilization of the volatile components in the solution and the change of the characteristics of the solution caused by the decomposition of the components can be suppressed.

[0153] From the viewpoint of the efficiency of removing particles and productivity, a filter having a pore size of 0.5 μm or less is used. In particular, from the viewpoint of the efficiency of removing particles, a membrane filter having a pore size of 0.1 μm is preferably used.

[0154] From the viewpoint of the efficiency of removing fine particles and productivity, the pressure during filtration is preferably 0.05 MPa to 0.6 MPa, and more preferably 0.1 MPa to 0.4 MPa.

[0155] It is preferable to confirm that the balance of the components contained in the precursor solution obtained after the filtration step is ensured due to the removal of fine particles.

[0156] Example

[0157] Hereinafter, the present invention will be described in detail with reference to Examples. In addition, the present invention is not limited to the following Examples.

[0158] [Comparative Example 1]

[0159] A hydrogen peroxide aqueous solution was prepared by adding 7.7 g of hydrogen peroxide aqueous solution having a concentration of 35% by mass to 19.6 g of pure water, and 4.4 g of niobic acid (Nb2O5·nH2O (Nb2O5 content: 58.0%)) was added to the hydrogen peroxide aqueous solution.

[0160] After adding niobic acid, the temperature of the liquid to which niobic acid was added was adjusted so that the liquid temperature was within the range of 20°C to 30°C.

[0161] To the liquid to which niobic acid had been added, 3.5 g of aqueous ammonia having a concentration of 28% by mass was added, and the mixture was sufficiently stirred in the atmosphere to obtain a transparent solution.

[0162] In a nitrogen atmosphere, 0.9 g of lithium hydroxide monohydrate (LiOH·H2O) was added to the obtained transparent solution to obtain a transparent aqueous solution containing a peroxo complex of niobium and lithium. The aqueous solution containing a peroxo complex of niobium and lithium was then allowed to stand at 25°C for about 6 hours.

[0163] When a precipitate is generated during standing, the aqueous solution containing the peroxide niobium complex and lithium is stirred to such an extent that the precipitate is dispersed, and then filtered through a membrane filter having a pore size of 0.1 μm, thereby obtaining a lithium niobate precursor solution described in Comparative Example 1.

[0164] The precursor solution described in Comparative Example 1 was subjected to (1) quantitative analysis of the amount of lithium and the amount of niobium, (2) quantitative analysis of the water content, (3) absorbance measurement, (4) evaluation of the surface energy of the solution, (5) evaluation of the polar component and the dispersion component in the surface energy of the solution, (6) evaluation of the contact angle on the LNCM (111) substrate, (7) evaluation of the contact angle on the LNM (13) substrate, (8) evaluation of the contact angle on the LNCM (811) substrate, and (9) evaluation of the coverage. Each measurement item is described below.

[0165] Among them, LNM (13) substrate refers to LiNi 1 / 2 Mn 3 / 2 O4 sputtering film-forming substrate is sometimes referred to as "LNM (13) substrate" in the present invention. In addition, LNCM (811) substrate refers to LiNi 4 / 5 Co 1 / 10 Mn 1 / 10 The O2 sputtering film-forming substrate is sometimes referred to as a "LNCM (811) substrate" in the present invention.

[0166] (1) Quantitative analysis of lithium and niobium content

[0167] The components of the precursor solution (Li content, M element content) were analyzed using inductively coupled plasma atomic emission spectrometry (ICP-AES, manufactured by Agilent Technologies, CP-720).

[0168] It should be noted that in the ICP-AES measurement, 0.1 g of the sample is accurately weighed, pure water and hydrochloric acid are added thereto and heated, then left to cool, and further hydrogen peroxide water is added and heated, then left to cool, and then the liquid volume is fixed to 100 mL, and after dilution, the measurement is performed using ICP-AES.

[0169] (2) Quantitative analysis of moisture content

[0170] The water content was determined by volumetric titration using a Karl Fischer titrator.

[0171] Specifically, a volumetric titration-type Karl Fischer titrator (MKA-610 manufactured by Kyoto Electronics Co., Ltd.) was used, (Composite 5K manufactured by Honeywell) was used as a titration solution, and (Medium K manufactured by Honeywell) was used as a solvent.

[0172] Then, after the solvent in the titration flask was anhydrous with the titration solution, the sample was directly added to measure the water content. The results are shown in Table 1.

[0173] (3) Absorbance measurement

[0174] 3.5 mL of the precursor solution was taken into a quartz cuvette (10 mm×10 mm×45 mm), and the absorbance at a wavelength of 400 to 700 nm was measured using an ultraviolet-visible spectrophotometer (SHIMADZU, UV-1800). The temperature of the precursor solution during the measurement was set at 25°C.

[0175] At this time, the absorbance zero point is the absorbance when 25° C. ultrapure water having an electrical conductivity of 17 MΩ·cm or more is added to a measurement cuvette and measured.

[0176] The results of the absorbance at a wavelength of 660 nm are shown in Table 2. The absorbance at a wavelength of 660 nm indicates the intensity of scattered light from the fine particles in the precursor solution, and a high absorbance means a high fine particle concentration (see JIS-K0101).

[0177] In addition, the absorbance at a wavelength of 400 nm means the concentration of fine particles with a smaller particle size and anions compared to the absorbance at a wavelength of 660 nm.

[0178] (4) Evaluation of solution surface energy

[0179] The surface tension of the precursor solution was measured at 25° C. using an automatic surface tensiometer CBVP-Z manufactured by Kyowa Interface Science Co., Ltd., and the value was taken as the surface energy value.

[0180] (5) Evaluation of the polar and dispersive components of the surface energy of solutions

[0181] The slide glass was immersed in paraffin (Fujifilm Wako Pure Chemical Industries, Ltd., reagent grade 1) melted at 90°C on a hot plate, taken out and slowly cooled in air at 25°C to prepare a paraffin substrate. The surface roughness Ra measured using a shape measurement laser microscope (Keyence Corporation, VK-9710) was 15.181 μm.

[0182] About 10 μL of the precursor solution was dropped onto the substrate in the air under the conditions of the paraffin substrate temperature of 25° C. and the solution temperature of 25° C., and the contact angle after 3 seconds was determined by the θ / 2 method.

[0183] The contact angles obtained, the surface energies of the solutions measured in "(4) Evaluation of the surface energies of solutions", and the literature value of the surface energy of alkanes (surface energy: γ = 25.5 mJ / m 2 , the dispersion component of surface energy: γ d =25.5mJ / m 2 , the polar component of surface energy: γ p =0.00mJ / m 2 ), and the Young-Dupre formula was used to calculate the dispersion component and polar component values ​​in the surface energy of the precursor solution. The results are shown in Table 2.

[0184] (6) Contact angle evaluation on LNCM (111) substrate

[0185] Preparation of LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 sputtering film-forming substrate (Toyoshima Manufacturing Co., Ltd., target film thickness: 50 nm, LNCM (111) substrate: SLG-25 mm, substrate smoothness: Ra is 0.021 μm, substrate is not heated).

[0186] In order to remove moisture attached to the surface of the LNCM (111) substrate, the substrate was heat treated at 220°C for more than 1 hour in a vacuum (gauge pressure: below -0.1 MPa), then slowly cooled to room temperature in a vacuum and stored in a N2 atmosphere.

[0187] In order to suppress the influence of moisture adhesion in the atmosphere, the contact angle was evaluated within 5 minutes after the substrate was taken out of the N 2 atmosphere.

[0188] About 10 μL of the precursor solution was dropped onto the LNCM (111) substrate in the air at a substrate temperature of 25° C. and a solution temperature of 25° C., and the contact angle was determined 3 seconds later by the θ / 2 method.

[0189] (7) Contact angle evaluation on LNM (13) substrate

[0190] Preparation of LiNi 1 / 2 Mn 3 / 2 O4 sputtering film-forming substrate (Toyoshima Manufacturing Co., Ltd., target film thickness: 50nm, LNM (13) substrate: SLG-25mm, substrate smoothness: Ra is 0.021μm, substrate unheated condition) (hereinafter sometimes referred to as LNM (13) substrate).

[0191] The contact angle was measured in the same manner as for the LNCM (111) substrate.

[0192] (8) Contact angle evaluation on LNCM (811) substrate

[0193] Preparation of LiNi 4 / 5 Co 1 / 10 Mn 1 / 10 O2 sputtering film-forming substrate (Toyoshima Manufacturing Co., Ltd., target film thickness: 50nm, LNCM (811) substrate: SLG-25mm, substrate smoothness: Ra is 0.021μm, substrate unheated condition) (hereinafter sometimes referred to as LNCM (811) substrate).

[0194] Using this LNCM (811) substrate, the contact angle of the precursor solution was measured in the same manner as the LNCM (111) substrate. The results are shown in Table 2.

[0195] (9) Evaluation of coverage rate

[0196] The evaluation method of the coverage rate of the coating film on the surface of the electrode active material is described in the order of <1> preparation of a slurry containing an electrode active material and a precursor solution, <2> preparation of a precursor of the electrode active material to be coated, <3> preparation of the coated electrode active material, and <4> evaluation of the coverage rate.

[0197] <1> Preparation of slurry containing electrode active material and precursor solution

[0198] LiNi as the positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 40.0 g of O2 as an electrode active material was put into a beaker, and 23.3 g of a sample solution of a precursor solution was further added thereto, followed by stirring with a magnetic stirrer to prepare a slurry.

[0199] <2> Preparation of Precursor of Coated Electrode Active Material

[0200] The prepared slurry was supplied to a spray dryer (Micro Spray Dryer B-290 manufactured by BUCHI) at a rate of 0.5 g / sec using a liquid feeding pump, and the slurry droplets were dried by air flow to recover the coated precursor of the electrode active material.

[0201] Here, the operating conditions of the spray dryer are as follows.

[0202] Air supply temperature: 200℃

[0203] Air supply volume: 0.45m 3 / min

[0204] <3> Preparation of coated electrode active material

[0205] The precursor of the electrode active material to be coated was calcined at 200° C. for 5 hours using a muffle furnace to synthesize lithium niobate on the surface of the electrode active material, thereby obtaining a coated electrode active material.

[0206] 〈4〉Coverage evaluation

[0207] The coated electrode active material was subjected to surface element analysis using an X-ray photoelectron spectrometer (X-tool, manufactured by ULVAC-PHI).

[0208] And, according to Nb 3d 、Ni 2p3 、Co 2p3 , Mn 2p3 The element ratio on the surface was determined from the values ​​of various peaks, and the niobium concentration on the surface of the coated electrode active material was calculated according to the following formula.

[0209] (In the following formula, each element symbol represents the ratio [atomic %] of each element.)

[0210] Niobium concentration on the surface of the electrode active material (%) = (100 × Nb) / (Ni + Co + Mn + Nb) ... (Formula)

[0211] The calculated niobium concentration on the surface of the electrode active material described in Comparative Example 1 was used as a reference value. Table 2 shows that the niobium concentration on the surface of the electrode active material described in Comparative Example 1 was used as a "reference value".

[0212] In addition, when the electrode active material also contains the M element in the precursor solution, the mole fraction of the M element constituting the electrode active material is subtracted from the mole fraction of the M element in the denominator and numerator of the above formula and calculated, so that the coverage rate can be obtained. Here, the mole fraction of the M element constituting the electrode active material can be obtained by etching the lithium oxide coating layer of the coated electrode active material using an appropriate method and measuring it using X-ray photoelectron spectroscopy. As an etching method, for example, an ion sputtering device attached to an X-ray photoelectron spectroscopy device is used to etch the coated electrode active material by about 100nm in terms of M element oxide conversion.

[0213] [Example 1]

[0214] In the same manner as in Comparative Example 1, a solution containing a peroxo complex of niobium and lithium was prepared.

[0215] 0.3 g of 1,2-propylene glycol (special grade reagent) was added to 29.7 g of the prepared solution containing the peroxo complex of niobium and lithium, and the temperature was adjusted so that the liquid temperature was in the range of 20°C to 30°C while stirring for more than 10 minutes to obtain the lithium niobate precursor solution described in Example 1.

[0216] The precursor solution described in Example 1 was subjected to the following procedures in the same manner as in Comparative Example 1: (1) quantitative analysis of the amount of lithium and the amount of niobium, (2) quantitative analysis of the amount of water, (3) absorbance measurement, (4) evaluation of the surface energy of the solution, (5) evaluation of the polar component and the dispersion component in the surface energy of the solution, (6) evaluation of the contact angle on an LNCM (111) substrate, (7) evaluation of the contact angle on an LNM (13) substrate, and (8) evaluation of the contact angle on an LNCM (811) substrate. The results are shown in Tables 1 and 2.

[0217] (9) Evaluation of the coverage ratio was also carried out in the same manner as in Comparative Example 1, and the niobium concentration on the surface of the electrode active material described in Example 1 was calculated. It was found that the niobium concentration on the surface of the electrode active material described in Example 1 increased by +5% relative to the reference value calculated in Comparative Example 1. Therefore, the increase in niobium concentration, i.e., +5%, was taken as the relative value of the increase in coverage ratio, and the results are shown in Table 2.

[0218] [Example 2]

[0219] The lithium niobate precursor solution described in Example 2 was obtained by performing the same operation as in Example 1 except that 3.0 g of 1,2-propylene glycol (reagent special grade) was added to 27.0 g of the solution containing the peroxo complex of niobium and lithium.

[0220] The precursor solution described in Example 2 was subjected to the same evaluation as in Comparative Example 1 and Example 1. The results are shown in Tables 1 and 2.

[0221] Furthermore, for Example 2, the absorbance measurement results of the precursor solution at a wavelength of 400 nm are shown in Table 2, and the absorbance measurement results at wavelengths of 400 to 700 nm are shown in Table 2 as a black solid line. Figure 4 .

[0222] [Example 3]

[0223] The lithium niobate precursor solution described in Example 3 was obtained by performing the same operation as in Example 1 except that 0.3 g of 1-butanol (reagent special grade) was added to 29.7 g of the solution containing the peroxo complex of niobium and lithium.

[0224] The precursor solution described in Example 3 was subjected to the same evaluation as in Comparative Example 1 and Example 1. The results are shown in Tables 1 and 2.

[0225] [Example 4]

[0226] The lithium niobate precursor solution described in Example 4 was obtained by the same operation as in Example 1 except that 0.03 g of FTERGENT 222F (manufactured by NEOS) was added to 29.97 g of the solution containing the peroxo complex of niobium and lithium instead of adding 1,2-propylene glycol.

[0227] The precursor solution described in Example 4 was subjected to the same evaluation as in Comparative Example 1 and Example 1. The results are shown in Tables 1 and 2.

[0228] [Example 5]

[0229] The lithium niobate precursor solution described in Example 5 was obtained by the same operation as in Example 1 except that 0.3 g of FTERGENT 222F (manufactured by NEOS) was added to 29.7 g of the solution containing the peroxo complex of niobium and lithium instead of adding 1,2-propylene glycol.

[0230] The precursor solution described in Example 5 was subjected to the same evaluation as in Comparative Example 1 and Example 1. The results are shown in Tables 1 and 2.

[0231] Furthermore, for Example 5, the absorbance measurement results of the precursor solution at a wavelength of 400 nm are shown in Table 2, and the absorbance measurement results at wavelengths of 400 to 700 nm are shown in Table 2 as a gray solid line. Figure 4 .

[0232] [Example 6]

[0233] The lithium niobate precursor solution described in Example 6 was obtained by performing the same operation as in Example 1, except that 0.3 g of LEOCOL TD-120 (manufactured by Lion Corporation) was added to 29.7 g of the solution containing the peroxo complex of niobium and lithium instead of adding 1,2-propylene glycol.

[0234] The precursor solution described in Example 6 was subjected to the same evaluation as in Comparative Example 1 and Example 1. The results are shown in Tables 1 and 2.

[0235] [Example 7]

[0236] The lithium niobate precursor solution described in Example 7 was obtained by performing the same operation as in Example 1, except that 0.3 g of DEDG (manufactured by Nippon Emulsifier Co., Ltd.) was added to 29.7 g of the solution containing the peroxo complex of niobium and lithium instead of adding 1,2-propylene glycol.

[0237] The precursor solution described in Example 7 was subjected to the same evaluation as in Comparative Example 1 and Example 1. The results are shown in Tables 1 and 2.

[0238] [Comparative Example 2]

[0239] A lithium nitrate aqueous solution was prepared by adding 0.16 g of lithium nitrate to 8.55 g of pure water. 0.80 g of niobium pentaethoxide and 0.03 g of EMULGEN 108 (Kao Corporation) were added to the lithium nitrate aqueous solution. The solution was stirred thoroughly in the atmosphere while adjusting the temperature of the liquid obtained by adding niobium pentaethoxide and EMULGEN 108 to the lithium nitrate aqueous solution so that the liquid temperature was within the range of 20°C to 30°C, thereby obtaining a turbid precursor solution as described in Comparative Example 2.

[0240] The precursor solution described in Comparative Example 2 was subjected to the same evaluation as in Comparative Example 1. The results are shown in Tables 1 and 2.

[0241] It should be noted that in the precursor solution described in Comparative Example 2, fine particles were generated due to the precipitation of the solute, so when the precursor of the coated electrode active material was prepared, the nozzle of the spray dryer was clogged and the coated electrode active material could not be prepared. Therefore, the evaluation of the coating rate (9) was not performed.

[0242] [Comparative Example 3]

[0243] 170 mL of pure water was mixed with 0.7226 g of lithium phosphate, and aqueous ammonia was added to adjust the pH to 10. The mixture was stirred well in the atmosphere while adjusting the temperature of the mixed solution of lithium phosphate and water to a range of 20° C. to 30° C. to obtain a transparent solution.

[0244] The obtained transparent solution was filtered through a membrane filter having a pore size of 0.1 μm, thereby obtaining the precursor solution described in Comparative Example 3, which is a solution containing lithium and phosphoric acid.

[0245] It should be noted that the absorbance of the precursor solution described in Comparative Example 3 is less than 0.001, which is the detection limit.

[0246] The precursor solution described in Comparative Example 3 was subjected to the same procedures as in Comparative Example 1: (1) quantitative analysis of lithium and phosphorus content, (2) quantitative analysis of water content, (3) absorbance measurement, (4) evaluation of surface energy of the solution, (5) evaluation of polar and dispersion components in the surface energy of the solution, (6) evaluation of contact angle on LNCM (111) substrate, (7) evaluation of contact angle on LNM (13) substrate, and (8) evaluation of contact angle on LNCM (811) substrate. The results are shown in Tables 1 and 2.

[0247] In addition, in the evaluation of the coverage rate (9), a sample solution of the precursor solution described in Comparative Example 3 is used in the preparation of a slurry containing an electrode active material and a precursor solution. Otherwise, the same operation as in Comparative Example 1 is performed to synthesize lithium phosphate on the surface of the electrode active material, thereby obtaining the coated electrode active material described in Comparative Example 3.

[0248] 〈Evaluation of coverage rate〉

[0249] The coated electrode active material was subjected to surface element analysis using an X-ray photoelectron spectrometer (X-tool, manufactured by ULVAC-PHI).

[0250] And, according to P 2p 、Ni 2p3 、Co 2p3 , Mn 2p3 The element ratio on the surface was determined from the values ​​of various peaks, and the phosphorus concentration on the surface of the coated electrode active material was calculated according to the following formula.

[0251] (In the following formula, each element symbol represents the ratio [atomic %] of each element.)

[0252] Phosphorus concentration on the surface of electrode active material (%) = (100×P) / (Ni+Co+Mn+P)……(Formula)

[0253] Then, the calculated phosphorus concentration on the surface of the electrode active material described in Comparative Example 3 was used as a reference value.

[0254] Table 2 shows the phosphorus concentration on the surface of the electrode active material described in Comparative Example 3 as a “reference value”.

[0255] [Example 8]

[0256] In the same manner as in Comparative Example 3, a solution containing lithium and phosphoric acid was prepared.

[0257] To 29.7 g of the obtained solution containing lithium and phosphoric acid, 0.3 g of EMULGEN 108 (manufactured by Kao Corporation) was added, and the mixture was stirred for 10 minutes or more while adjusting the liquid temperature to 20 to 30° C., thereby obtaining a precursor solution described in Example 8.

[0258] The precursor solution described in Example 8 was subjected to the same procedures as in Comparative Example 3, including (1) quantitative analysis of the amount of lithium and phosphorus, (2) quantitative analysis of the water content, (3) absorbance measurement, (4) evaluation of the surface energy of the solution, (5) evaluation of the polar component and the dispersion component in the surface energy of the solution, (6) evaluation of the contact angle on an LNCM (111) substrate, (7) evaluation of the contact angle on an LNM (13) substrate, and (8) evaluation of the contact angle on an LNCM (811) substrate. The results are shown in Tables 1 and 2.

[0259] Furthermore, for Example 8, the absorbance measurement results of the precursor solution at a wavelength of 400 nm are shown in Table 2, and the absorbance measurement results at wavelengths of 400 to 700 nm are shown in Table 2 by a black dotted line. Figure 4 .

[0260] In (9) Evaluation of the coverage, the same operation as in Comparative Example 3 was performed to calculate the phosphorus concentration on the surface of the electrode active material described in Example 8. It was found that the phosphorus concentration on the surface of the electrode active material described in Example 8 increased by +6% relative to the reference value calculated in Comparative Example 3. Therefore, the increase in phosphorus concentration, i.e., +6%, was used as the relative value of the increase in coverage, and the results are shown in Table 2.

[0261] [Summarize]

[0262] For the precursor solutions described in Examples 1 to 8 and Comparative Examples 1 and 3, the surface energy value is plotted on the horizontal axis and the relative value of the increase in coverage is plotted on the vertical axis. Figure 1 The relationship between the value of the surface energy polar component and the coverage rate is shown in the graph, with the value of the surface energy polar component as the horizontal axis and the relative value of the coverage rate increase as the vertical axis. Figure 2 .

[0263] according to Figure 1 It can be understood from the attached figure that for the precursor solution described in the embodiment, if the surface energy value is 72 mN / m or less, a sufficient coverage rate is exerted on the electrode active material.

[0264] In addition, according to Figure 2 It can also be understood from the figure that for the precursor solution described in the embodiment, if the value of the polar component of the surface energy is 45 mN / m or less, a high coverage rate is exerted on the electrode active material.

[0265] The relationship between the cosθ value and the coverage when the contact angle on the LNCM (111) substrate described in Examples 1 to 8 and Comparative Examples 1 and 3 is shown in FIG. Figure 3 .

[0266] according to Figure 3 The figure shows that: in LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 The value of cosθ when the contact angle on the O2 sputtering film-forming substrate is θ is proportional to the coverage. That is, it can be considered that: if the value of cosθ when the contact angle on the substrate of the precursor solution is θ is larger (the smaller θ is), the wettability of the electrode active material composed of the substrate is better, so when the precursor solution is applied to the surface of the electrode active material, it will be uniformly wetted and diffused, so the formed coating layer is uniformed and the coverage is improved. Specifically, it can be considered that: if the value of cosθ is greater than 0.5 (θ is less than 60°), the wettability is good.

[0267] [Table 1]

[0268]

[0269] [Table 2]

[0270]

Claims

1. A lithium-containing oxide precursor solution for forming a coating layer on the surface of a powder of an electrode active material, comprising 0.1 mass % or more and 5.0 mass % or less of Li, The invention contains 0.05 mass % or more and 35 mass % or less of at least one M element selected from the group consisting of Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, and I, contains 60 mass % or more and 98.4 mass % or less of water, The lithium oxide precursor solution used to form a coating layer on the surface of the electrode active material powder has an absorbance value of 0.1 or less at a wavelength of 660 nm. The value of the surface energy is 72 mN / m or less. 2 . The lithium-containing oxide precursor solution for forming a coating layer on the surface of a powder of an electrode active material according to claim 1 , wherein the value of the polar component of the surface energy is 0 mN / m or more and 45 mN / m or less.

3. The lithium oxide precursor solution for forming a coating layer on the surface of the powder of the electrode active material according to claim 1 or 2, wherein: The value of Li / M, which is a molar ratio of the Li to the M element, is 0.36 or more and 11.2 or less.

4. The lithium oxide precursor solution for forming a coating layer on the surface of the powder of the electrode active material according to claim 1 or 2, wherein: The value of Li / Nb, which is a molar ratio of the Li to the Nb, is 0.90 or more and 1.40 or less.

5. The lithium oxide precursor solution for forming a coating layer on the surface of the powder of the electrode active material according to claim 1 or 2, wherein: The value of Li / P, which is a molar ratio of the Li to the P, is 0.90 or more and 1.40 or less. 6 . The lithium-containing oxide precursor solution for forming a coating layer on the surface of a powder of an electrode active material according to claim 1 , wherein the surface energy value thereof is 15 mN / m or more and 40 mN / m or less. 7 . The lithium-containing oxide precursor solution for forming a coating layer on the surface of a powder of an electrode active material according to claim 1 , comprising 0.01 mass % or more and 20.0 mass % or less of a surfactant.

8. The lithium oxide precursor solution for forming a coating layer on the surface of the powder of the electrode active material according to claim 7, wherein: The surfactant is a nonionic surfactant.

9. A method for producing a lithium oxide precursor solution for coating an electrode active material, comprising the following steps: a dissolving step of dissolving lithium and at least one element selected from the group consisting of Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, and I in a solvent mainly composed of water that constitutes the lithium-containing oxide precursor solution for coating the electrode active material; and a surface energy adjustment step of adjusting the surface energy value of the water-based solvent constituting the lithium-containing oxide precursor solution for coating the electrode active material to 72 mN / m or less, in, The order of performing the dissolving step and the surface energy adjusting step is arbitrary.

10. A method for producing a lithium oxide precursor solution for coating an electrode active material, comprising the following steps: A dissolving step of dissolving lithium and at least one element selected from the group consisting of Nb, F, Fe, P, Ta, V, Ge, B, Al, Ti, Si, W, Zr, Mo, S, Cl, Br, and I in a solvent mainly composed of water that constitutes the lithium-containing oxide precursor solution for coating the electrode active material; a surface energy adjustment step of adjusting the surface energy value of the water-based solvent constituting the lithium-containing oxide precursor solution for coating the electrode active material to be 72 mN / m or less; and a filtering step of filtering the solution obtained after the dissolving step, in, The order of performing the dissolving step and the surface energy adjusting step is arbitrary.

11. The method for producing a lithium oxide precursor solution for coating an electrode active material according to claim 9 or 10, characterized in that: In the surface energy adjustment step, the value of the polar component in the surface energy is adjusted to be greater than or equal to 0 mN / m and less than or equal to 45 mN / m.

12. The method for producing a lithium-containing oxide precursor solution for coating an electrode active material according to claim 9 or 10, wherein: The value of the surface energy is adjusted by adding a surfactant.

13. The method for producing a lithium-containing oxide precursor solution for coating an electrode active material according to claim 12, wherein: The surfactant is a nonionic surfactant.

Citation Information

Patent Citations

  • Active material composite powder and lithium battery, and method for producing the same

    JP2015056307A

  • Electrolyte, battery, electronic apparatus, electrolyte and method for producing battery

    JP2019145261A

  • Binder composition for lithium ion secondary battery, slurry composition for lithium ion secondary battery, electrode for lithium ion secondary battery, lithium ion secondary battery, and method for producing binder composition for lithium ion secondary battery

    CN105122521A

  • Solution and method for manufacturing same, and method for manufacturing active material for secondary cell

    CN108778999A